Nominalizations in Nepali - Pokharel, Madhav Prasad (Nepalese Linguistics, 2025)
The first Nepali inscription (11th c.) starts with a noun-like sentence, a Noun Phrase. This paper reassesses Nepali nominalizations in the comprehensive framework offered in Shibatani (2019), which recognizes both classifying and non-classifying nominalizations. Besides lexical nominalizations creating nouns, there are grammatical nominalizations targeting five structures (numerals, demonstratives, genitives, adjectives and verb-based (V-based), each of which supplies metonymic meanings to the nominalized structures. There are two types (attributive and predicative) of V-based nominalizations, of which the diachronically predicative use of the V-based nominalization (-ta participle) is reanalyzed as a finite verb enriched with TAM markers. Even adverbs are nominalized. Multiple markers of nominalization give noun-like structures whose distribution generates numerous structures with both ‘expected’ and ‘unexpected’ functions. Some of the unexpected functions are citation form, purpose, nonrelative attribute, honorific, permission, command, prohibition, duty, volition, compulsion, general notice and modal. There is also a recursive use of nominalizers.